2015
DOI: 10.5535/arm.2015.39.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Needle Placement in Cadavers: Non-Guided Versus Ultrasound-Guided

Abstract: ObjectiveTo compare the accuracy rates of non-guided vs. ultrasound-guided needle placement in four lower limb muscles (tibialis posterior, peroneus longus, and short and long heads of the biceps femoris).MethodsTwo electromyographers examined the four muscles in each of eight lower limbs from four fresh frozen cadavers. Each electromyographer injected an assigned dye into each targeted muscle in a lower limb twice (once without guidance, another under ultrasound guidance). Therefore, four injections were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…However, in many clinical situations, such as studies in patients with stroke or cerebral palsy, the confirmation of insertion in the muscle is difficult due to inadequate muscle contraction. The results of a recent cadaver study suggest that ultrasound‐guided needle insertion into the tibialis posterior is more accurate than blind needle insertion . In addition, there were large anatomic variations among individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many clinical situations, such as studies in patients with stroke or cerebral palsy, the confirmation of insertion in the muscle is difficult due to inadequate muscle contraction. The results of a recent cadaver study suggest that ultrasound‐guided needle insertion into the tibialis posterior is more accurate than blind needle insertion . In addition, there were large anatomic variations among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent cadaver study suggest that ultrasoundguided needle insertion into the tibialis posterior is more accurate than blind needle insertion. 17 In addition, there were large anatomic variations among individuals. For example, the bony thickness at the midpoint for the anterior approach ranged from 0.79 to 3.56 cm.…”
Section: Discussionmentioning
confidence: 99%
“…58 In a cadaveric study, ultrasound greatly improved needle EMG placement accuracy in most muscles. 59 As well, a recent review showed that ultrasound guidance increased the success rates of lumbar puncture and reduced the procedural time in patients with poorly palpable landmarks related to obesity, prior spinal surgery, and other difficult clinical circumstances. 60 Further studies are needed to determine whether ultrasound may facilitate the delivery of novel disease-modifying treatment such as intrathecal injections for patients with SMA.…”
Section: Guiding Needle Placementmentioning
confidence: 99%
“…Furthermore, ultrasound can be used to guide needle EMG to distinguish muscles in close proximity, 55 and to enhance patient safety when needling the diaphragm, 56 the periscapular muscles, 57 or other muscles in patients on anticoagulants 58 . In a cadaveric study, ultrasound greatly improved needle EMG placement accuracy in most muscles 59 . As well, a recent review showed that ultrasound guidance increased the success rates of lumbar puncture and reduced the procedural time in patients with poorly palpable landmarks related to obesity, prior spinal surgery, and other difficult clinical circumstances 60 .…”
Section: Practical Uses Of Muscle Ultrasoundmentioning
confidence: 99%
“…Ultrasound guidance of Botulinum toxin injection is the author's preferred method as it simultaneously allows selective muscle injection and confirmation of the target injected. Dynamic EMG-guided Botulinum toxin injection is also used, but this is less selective and less specific (65).…”
Section: Surgical Optionsmentioning
confidence: 99%